PHYSIOLOGICAL RESPONSES OF BLOOD AND IMMUNE ORGANS OF BROILER CHICKEN FED DIETARY BLACK CUMIN POWDER (Nigella sativa) DURING DRY SEASONS - Salam, S.; Sunarti, D.; Isroli, I. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
This study was designed to determine the physiological response of blood and immune organs ofbroiler chickens fed on various concentration of dietary black cumin powder (BCP) during the dryseason. A total number of 100 unsexed one-day old Cobb broiler chicks were used and distributed to 5treatments (control, antibiotics and without BCP, 20 g/kg BCP, 40 g/kg BCP and 60 g/kg BCP) and 4replications (5 birds for each). Physiological responses of blood and immune organs were measured at30 day of age. Addition of BCP to broiler ration did not significantly effects on physical properties ofblood (leukocytes count, erythrocytes count, haemoglobin, hematocrit, monocytes, and eosinophils) andrelative weights of thymus and bursa of fabricius, but significantly (P<0.05) increased relative weightsof spleen when compared to control. It was concluded that the black cumin grinds (Nigella sativa) as afeed additive could not change the physical properties of blood, relative weights of thymus and bursa offabricius, but it increased the relative weight of spleen at the level of 60 g/kg BCP, which could reduceadverse effects of infectious diseases in broiler chicken.